THE ROLE OF ICT IN COMBATING CYBERCRIMES: A STUDY FROM ABRAKA, DELTA STATE, NIGERIA - Adebayo, Olumide Bola (International Research Journal of Arts and Communication, 2025)
This study investigated Information and Communication Technology (ICT) and its impact in combating cybercrimes in Abraka, Delta State as a case study. In order to achieve the purpose of this study, questionnaire was used to elicit information from the respondents. The sample size for the study is one hundred and five (105), which constituted 10% of the entire population. The data collected were critically analyzed and the major findings revealed the following: that yahoo attack (also called 419) and hacking are the most prevalent cybercrimes in rural communities, that financial losses and abandonment of rural communities by government are the major impacts of cybercrime in rural areas, that unemployment and quest for wealth are the major cause of cybercrimes in rural communities. Finally, recommendations were made that control measures should be adopted by the various agencies concerned in order to curb cybercrimes in rural communities